2010
DOI: 10.1016/j.gene.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Screening of human gene promoter activities using transfected-cell arrays

Abstract: Promoters are the best characterized transcriptional regulatory sequences in complex genomes because of their predictable location immediately upstream of transcription start sites. Despite a substantial body of literature describing transcriptional promoters, the identification of true start sites for all human transcripts is far from complete. The same is true of the key structural and functional elements responsible for promoter action in different cell types. In order to identify elements responsible for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Then, a secondary PCR was performed with Gateway adapter primers (Invitrogen), followed by PEG-8000 precipitation of PCR products. The modified reporter gene vector pZsGreen1-1 and the control plasmid pHcRed1-N1 were used as described before (9). PCR products were cloned into the pZsGreen vector using Gateway BP Clonase II Enzyme Mix (Invitrogen) and transformed into competent TOP10 cells following the manufacturer’s recommendations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, a secondary PCR was performed with Gateway adapter primers (Invitrogen), followed by PEG-8000 precipitation of PCR products. The modified reporter gene vector pZsGreen1-1 and the control plasmid pHcRed1-N1 were used as described before (9). PCR products were cloned into the pZsGreen vector using Gateway BP Clonase II Enzyme Mix (Invitrogen) and transformed into competent TOP10 cells following the manufacturer’s recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…Samples for array spotting were prepared as previously described (9). Effectene reagent (Qiagen) with Enhancer (Qiagen) was used as transfection agent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioassays utilizing reporter vectors regulated by promoters of cellular stress-responsive gene have been suggested as promising tools to assess photocytotoxic (Cheng et al 2010). A recent study has shown that MCF-7 cells containing a human HSPA1A promoter-driven luciferase reporter could be used for assessing oxidative stress associated with low-dose photodynamic therapy (Zheng et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bioassays using reporter vectors regulated by cellular stress-responsive gene promoters have been suggested as promising tools for photocytotoxic assessment (Cheng et al 2010). The expression of significant stress responsiveness of HSPA1A is often regarded as a potential biomarker to evaluate oxidative cytotoxicity (Demirovic and Rattan 2012;Xin et al 2012).…”
Section: Introductionmentioning
confidence: 99%